Quality control and purification of ready-to-use conjugated gold nanoparticles to ensure effectiveness in biosensing - Wang, Junjie; Giordani, Stefano; Marassi, Valentina; Roda, Barbara; Reschiglian, Pierluigi; Zattoni, Andrea (Frontiers in Sensors, 2022)
Gold nanoparticles (AuNPs) and their conjugates are used for many applications in the field of sensors. Literature lacks procedures able to separate, purify and characterize these species in native conditions without altering them while assuring a high throughput. This technological gap can be reduced by exploiting Asymmetrical Flow Field Flow Fractionation multidetection platforms (AF4 multidetection). This work describes a complete set of strategies based on the AF4 system, from nanoparticle synthesis to separative method optimization to conjugates screening and characterization, to achieve quantitative control and purification of ready-to-use conjugated Gold nanoparticles and ensure effectiveness in biosensing. AF4-multidetection was used to study AuNPs with different types of surface coating (PEG and Citrate), their binding behavior with protein (BSA) and their stability of after conjugation to BSA. Attention was put into developing a robust but flexible method, able to be applied to different AuNPs and conjugating molecules. Morphology and conjugation mechanism were also evaluated thanks to the combination of batch and online sizing techniques, which is extremely important for quantitative control during bio-probe synthesis and subsequent bioassays.